A Cross-Sectional Survey on the Post-Pandemic Acceptability of Pharmacist-Delivered Telehealth Services Among HCV-HIV Patients - Rachel K. Mayaka Bpharm, MBA, PhD; Mary K. Awuonda PhD; Earl Ettienne BPharm, MBA, LPD; Monika Daftary PharmD; La'Marcus Wingate PharmD, PhD; Jacqueise Unonu PharmD (SAGE Publishing, 2023)
The COVID-19 pandemic enhanced the use of telehealth as a means of delivering services to patients who required continued and uninterrupted care. This helped to reduce readmission to hospitals where COVID-19 hospitalization was prioritized. Patients with HCV and HIV and other chronic diseases require this type of care. This study evaluated the post-pandemic acceptability of pharmacist-delivered telehealth services among HCV and HIV monoinfected and coinfected patients in Washington DC. This was a cross-sectional study conducted in a community pharmacy setting in Washington DC whose primary outcome was the acceptability of pharmacist-delivered telehealth services through a proposed platform(docsink). A validated questionnaire, borrowed from the literature was used to determine telehealth acceptability, measured as behavioral intention, among patients who receive care from this pharmacy. The study recruited 100 participants. Descriptive statistics were conducted as well as bivariable and multivariable analyses to assess predictors of telehealth acceptability. In the unadjusted model, PU/EM (OR 0.571, 95% confidence interval (0.45-0.73), P  < .0001)), PEOU(OR 0.72, 95% confidence interval (0.61-0.85)) and IM(OR 0.733, 95% confidence interval (0.62-0.87), P  = .0003)) were significant predictors of behavioral intention. Overall, the study found that lower Perceived Usefulness/Extrinsic Motivation scores decrease the odds of intending to use pharmacist-delivered telehealth (OR = 0.490, 95% confidence interval (0.29-0.83), P  = .008). This study determined that the impact of perceived usefulness and extrinsic motivation was critical to the acceptance of pharmacist-delivered telehealth among a predominantly Black/African American study population.